Analisis Brand Experience Dan Brand Personality Terhadap Customer Loyalty Produk Sim Card PT. Smartfren Telecom Tbk - Illiyin Dihan Prameswari; Praptini Yulianti (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
The objective of this research is to investigate the impact of (X1: Brand Experience) and (X2: Brand Personality) on (Y: Customer Loyalty). The sample consists of fifty respondents, and a Likert scale is used to measure the data quantitatively. This study used primary data obtained via online questionnaire responses, and conducted tests to assess validity, reliability, and hypotheses. The inquiry findings suggest that these factors, together with their interaction, have a significant and favorable impact on consumer loyalty. The t-test revealed that the significance value (sig) was below 0.05, indicating statistical significance. Additionally, the F-test showed that the calculated F-value exceeded the crucial F-value of 3.19. These data indicate that consumer loyalty (Y) is favorably and substantially affected by both brand experience (X1) and brand personality (X2).